ANALISIS PROSEDUR PENGELOLAAN PENGADAAN BARANG (METODE PEMBAYARAN UP) DAN KEWAJIBAN PERPAJAKANNYA DI PENGADILAN TINGGI BANDUNG - Luqman Ali Al-ghifari; Gunardi Gunardi; Priatna Kesumah; Dodi Syaripudin (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
This study examines the Analysis of goods procurement procedures and the collection mechanism of Tax Obligations at Pengadilan Tinggi Bandung. Using a descriptive qualitative approach through interviews, observations, and document analysis, the research reveals that the institution has implemented a procurement system divided into two payment methods: Uang Persediaan (UP) for transactions below Rp10 million and SPM-LS for higher-value transactions. The procurement process demonstrates good governance in terms of planning, execution, and financial accountability. However, discrepancies were found in the reporting of PPh 22 periodic tax returns through the DJP Online system, attributed to human resource limitations, heavy workload of treasury staff, and technical issues with computer equipment. Regarding supervision, the role of the Tax Office was deemed suboptimal in monitoring compliance. The study recommends improvements to the electronic reporting system, human resource capacity building through training, and strengthening both internal and external monitoring mechanisms to ensure tax compliance.